THE ESSENCE OF ISLAMIC EDUCATION: ONTOLOGY, AXIOLOGY, AND EPISTEMOLOGY - Okky, Okky Ria vinola; Zaidah, Nur; Mukarromah, Wahdatul Rike Uyunul; Assefa, Yalelam (EDUCATUM: Scientific Journal of Education, 2025)
This research aims to examine the essence of Islamic education through a philosophical approach that includes aspects of ontology, epistemology, and Axiology. In the ontological aspect, the research explores the nature of Islamic education as the process of forming kamil human beings based on human relations with God and the purpose of creation. Epistemological aspects examine the sources, methods, and validity of knowledge in Islamic education, especially the integration of Revelation and reason in the development of educational science. While the axiological aspect highlights the moral and ethical values that are the basis for the formation of the character of students in Islamic education. The research method uses a qualitative approach with literature studies and philosophical analysis of the main literature such as the Qur'an, Hadith, and works of Islamic educational philosophy. The results showed that Islamic education is not only the transfer of knowledge, but also the formation of integral spiritual and moral values, resulting in Noble and civilized individuals. These findings provide a strong conceptual basis for the development of a holistic Islamic educational practice and oriented to the formation of character and the development of full human potential.